EVALUASI DAMPAK PERDA NO. 06 TAHUN 2009 MENGENAI KEPEMILIKAN SIUP (SURAT IZIN USAHA PERDAGANGAN) TERHADAP PERTUMBUHAN USAHA PRODUSEN BATIK DI KOTA SEMARANG - SM. Angga Manggala Putra; Fathurrohman Fathurrohman; Slamet Santoso (Journal of Public Policy and Management Review, 2013)
Economic development for business growth based on local potential must supported by legality. SIUP as a legal instrument are expected to provide certainty and trade orderliness so efforts to controlled trading activity can be optimized.This studies measures the impact of SIUP to business growth the batik producers in Semarang City. Using descriptive qualitative method single program after – only, tried to explain that SIUP have positive impact for business growth especially in batik producers in Semarang City. Business growth increase resource productivity and increase the efficiency of trade.